Jamaica Customs Act : WTO Trade Facilitation Agreement Gap Analysis - World Bank Group (World Bank, Washington, DC, 2019)
This paper reviews the alignment of the customs act of Jamaica to the World Trade Organization (WTO) Trade Facilitation Agreement (TFA) and recommends changes where gaps are identified. In part II of this paper, the customs act is reviewed against each of the TFA technical measures, in order given in the agreement. Part III of the paper is a conclusion and summarizes the gaps and proposals of part II.